Aquaculture Wastewater Treatment Using A Combination Of Ozonation Process And Activated Carbon Adsorption - Mohd Shukri, Farah Anis (Universiti Sains Malaysia, 2021)
This study investigates the effectiveness of ozonation treatment alone and combination of ozonation treatment with activated carbon adsorption to treat the synthetic aquaculture wastewater. The solution of a synthetic dye, methylene blue was ozonated using an ozone generator in order to illustrate the color removal of aquaculture wastewater. The experiment was conducted under a constant ozone dosage of 600 mg/h and the concentration was observed throughout 60 minutes. The factors affecting the process of degradation were investigated, i.e., the effects of initial dye concentration (mg/L) and effects of pH. Apart from that comparison between ozonation and ozonation-activated carbon adsorption was observed. The ozonation was done in 1L beaker with 500 mL dye solution. The initial concentration studied in this work were 30 mg/L, 45 mg/L and 60 mg/L meanwhile pH 3, pH 7 and pH 9 for pH studies. As a result, the initial dye concentration of 60 mg/L took the longest reaction time to achieve 90% of color removal efficiency followed by 45 mg/L and 30mg/L. This happened as ozone became the limiting substances in the reaction since the ozone dosage supplied was kept constant. Eventually, within 60 minutes, all color were successfully removed for all the initial concentrations. Apart from that, the degradation of methylene blue with ozone treatment had the highest color removal at pH 9 which was under basic condition and the lowest at pH 3 which was under acidic condition. Ozonation performed best under alkaline condition as more hydroxyl radicals could be generated compared in acidic condition. Besides that, the rate of degradation was enhanced with the combination of activated carbon adsorption and ozonation treatment.